Análisis de los factores que determinan la sostenibilidad y sustentabilidad de la economía social y solidaria para la crianza y comercialización de porcinos en pie y faenado en los cantones Santo Domingo y Rumiñahui - Albán Fuentes, Andrea Carolina (2013)
The social and solidary economy takes as an initiative the persons association engaged in the same activity, such as associate in cooperatives, associations and other forms of organization in order to reach a common good; and also meet their needs through the union of human, material and economic resources so that they become competitive against larger producers. In the case of pork producers associations, the activities of production process are developed in a rudimentary way that it's not often appropriate. This is because they do not have the technological resources necessary to improve pork production and likewise create jobs for other people that help the country’s economic grow.